How to Recover Halal Tourism Sectors Post-Covid-19 in Jakarta - Lubis, Deni; Dzakirah, Jihan Qonitah; Mahanani, Yekti; Nursyamsiah, Tita (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2023)
Tourism is one of the industries most impacted by COVID-19, while DKI Jakarta is one of Indonesia’s biggest Muslim-friendly tourist destinations. This study aims to formulate a halal tourism recovery strategy post-COVID-19 with an approach to evaluate the strengths, weaknesses, opportunities, and threats of developing recovery plans in Jakarta, the biggest city in Indonesia. An analytical network process with a SWOT network structure was employed. In this method, many respondents are not needed, but what is needed is representation from experts in the field. The survey was conducted with five expert respondents, from academics, practicians, and regulators. The results showed that the benefits of the existing infrastructure, accessibility, and amenities greatly influenced the strength factor. The most significant shortcoming of halal tourism is that it remains misunderstood. Halal tourism, which is appropriate for use during the new normal period, is one of the most important opportunities and risks. There are no standards for organizing, controlling, and reducing the impact of epidemics/disasters on the tourism industry. According to SWOT analysis, priorities for halal tourism recovery strategies include strengthening halal tourism branding, international industrial infrastructure development, increased competitiveness, and service innovation related to halal products and services.